2012
DOI: 10.1007/s00392-012-0465-x
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α, myocardial perfusion and function in patients with ST-segment elevation myocardial infarction and primary percutaneous coronary intervention

Abstract: Our data reflect the clinical significance of early TNF-α elevation in patients with STEMI and primary PCI (Controlled Clinical Trials number, NCT00529607).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 107 publications
3
10
0
Order By: Relevance
“…Prior clinical and experimental studies have shown that resistin may promote the inflammatory process via upregulating the expression of proinflammatory cytokines, including TNF-α, interleukin-6, and monocyte chemoattractant protein-1 [5,22]. TNF-α and MIF levels upon admission all participate in the process of IRI [19,23,24], and our present research indicated for the first time that resistin at admission correlated positively with them in STEMI patients. In addition to inflammation, previous studies revealed that oxidative stress also contributed to IRI via reactive oxygen species (ROS) [20,21,25].…”
Section: Discussionsupporting
confidence: 65%
“…Prior clinical and experimental studies have shown that resistin may promote the inflammatory process via upregulating the expression of proinflammatory cytokines, including TNF-α, interleukin-6, and monocyte chemoattractant protein-1 [5,22]. TNF-α and MIF levels upon admission all participate in the process of IRI [19,23,24], and our present research indicated for the first time that resistin at admission correlated positively with them in STEMI patients. In addition to inflammation, previous studies revealed that oxidative stress also contributed to IRI via reactive oxygen species (ROS) [20,21,25].…”
Section: Discussionsupporting
confidence: 65%
“…Higher levels of neopterin are associated with the development of left ventricular dysfunction [ 31 ] and left ventricular remodelling [ 32 ] in patients with STEMI. TNF- α is rapidly released from resident mast cells and macrophages during MI [ 33 ] and its level is correlated closely with the extent of MI [ 34 ]. Our results showed a significant association between tertiles of PTX3 levels and those of neopterin and TNF- α and also significant but weak correlation between PTX3 at 24 h and level of neopterin and TNF- α in whole group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of TNF-α and its receptors are elevated also in patients with acute myocardial infarction and can predict infarct size, LV dysfunction and prognosis [22, 34, 35]. A study by Kehmeier et al showed that TNF-α levels measured in STEMI patients after PCI can predict infarct size [34].…”
Section: Main Textmentioning
confidence: 99%
“…A study by Kehmeier et al showed that TNF-α levels measured in STEMI patients after PCI can predict infarct size [34]. Nilsson et al measured soluble TNF-receptors in STEMI patients prior to and 24 h after PCI and showed that concentrations of TNFR1 and TNFR2 are associated with infarct size and LV dysfunction [22].…”
Section: Main Textmentioning
confidence: 99%